Experimental and theoretical studies of the properties of coherent Smith-Purcell radiation - Bakkali Taheri, F; Konoplev, I; Doucas, G; Reichold, A; Bartolini, R; Delerue, N; Barros, J; Clarke, C (Joint Accelerator Conferences Website (JACoW), 2016)
Recent advances in physics of particles accelerators and lasers have shifted dramatically the expectations of bunch length and capability to generate electron bunches with specific longitudinal profiles [1,2]. This has stimulated interest in analysis of spectrum of coherent radiation to enable the longitudinal bunch profile diagnostics at femtosecond-scale. Spectral analysis of coherent Smith- Purcell radiation (cSPr) is particularly relevant as it allows non-invasive and cost-effective monitoring of electron bunch profiles. In this paper, the recent results observed from the E203 experiment (FACET, SLAC) are presented. Consistency of the cSPr as diagnostic tool is discussed, as well as the properties of cSPr such as directionality and polarization.